2019
DOI: 10.1186/s12882-019-1391-1
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Klotho is associated with mortality and cardiovascular events in hemodialysis

Abstract: Background Klotho is a transmembrane protein acting as a co-receptor for FGF-23 and thus exerts clinical actions on mineral metabolism. The association of secreted Klotho with outcomes in CKD patients is unclear. This study examined the relation between plasma Klotho and cardiovascular events in dialysis patients, accounting for common and CKD-MBD related risk factors, arterial stiffness and atherosclerotic burden. Methods Seventy-nine chronic hemodialysis patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 39 publications
5
51
0
2
Order By: Relevance
“…In dialysis patients, Marçais et al [101] reported that conservation of serum Klotho above 280 ng/L is associated with a better 2-year cardiovascular protection. This is consistent with a recent prospective study -lower serum level of Klotho is associated with cardiovascular events in hemodialysis patients [102]. In CKD patients without dialysis, we demonstrated that lower serum Klotho levels are independently associated with overall mortality and CVD events [103].…”
Section: The Prospect Of Clinical Application Of Klotho In Ckd-associsupporting
confidence: 93%
“…In dialysis patients, Marçais et al [101] reported that conservation of serum Klotho above 280 ng/L is associated with a better 2-year cardiovascular protection. This is consistent with a recent prospective study -lower serum level of Klotho is associated with cardiovascular events in hemodialysis patients [102]. In CKD patients without dialysis, we demonstrated that lower serum Klotho levels are independently associated with overall mortality and CVD events [103].…”
Section: The Prospect Of Clinical Application Of Klotho In Ckd-associsupporting
confidence: 93%
“…Традиционные факторы риска кардиоваскулярных заболеваний, такие как артериальная гипертензия (АГ), дислипидемия, сахарный диабет, достаточно характерны для популяции больных ХБП. Однако в последние годы показано, что другие кардиоваскулярные факторы риска, специфичные для уремии, могут вносить вклад в увеличение сердечно-сосудистого риска при ХБП [3][4][5]. Эти факторы включают среди других изменение уровня морфогенетических белков (фактор роста фибробластов 23 -FGF-23, Klotho) и гликопротеина склеростина, которые участвуют в поддержании костно-минерального гомеостаза.…”
Section: ââåäåíèåunclassified
“…In patients with CKD 3 stage, a change in FGF23/klotho ratio correlated with the changes in left ventricular mass [114]. In hemodialysis patients, low klotho levels were associated with CV events, independently from other CKD-MBD factors [115]. Analysis of the LURIC (Ludwigshafen Risk and Cardiovascular Health) study did not show any additional predictive power of CV and mortality risk in patients with normal kidney function [116].…”
Section: Role Of Klothomentioning
confidence: 95%